Online Learning during Pandemic: Students' Motivation, Challenges, and Alternatives - Afif Ikhwanul Muslimin; Fitrana Harintama (Loquen, 2020)
AbstractPandemic had intrigued the change of EFL learning mode in higher education. The students had to adjust to the situation that created learning challenges that might obstruct learning progress. Furthermore, students’ motivations and creativities would lead them to find alternatives. Hence, the present study was aimed to investigate the students’ challenges, motivations, and alternatives. It was a descriptive qualitative research case study by gathering students’ responses using questionnaires and interview with 10 students who joined KSP (short course) English Syntax using WhatsApp group at English Education Study Program of UIN Mataram in July 2020. The results showed that students’ motivations were increasing scores in remedy class (90%) and gaining more science understanding (10%). The challenges faced by students during the online courses were poor internet connection (50%), simultaneous agendas (30%), limited WhatsApp feature (10%), and anxiety (10%). Regarding challenges, students did alternatives such as preparing phone credits (30%), praying for the end of the pandemic (10%), learning extensively (10%), searching for the best place to get an internet signal (20%), setting alarm (10%), and creating on-going motivation (20%). The research showed that online mode learning needed adequate preparations mentally, physically, and financially to back up their learning deficiency.Keywords: Online learning; EFL; Motivations; Covid-19; Education